(untitled) (World Bulletin of Public Health, 2026)
This paper analyzes the anthropogenic pollution of water resources by heavy metals, which represent a significant environmental threat. The study systematizes data on the chemical forms and migration pathways of metals within the hydrosphere, while also outlining current maximum permissible concentration (MPC) standards. Primary focus is placed on innovative biopurification methods, specifically phytoremediation and biosorption. The author demonstrates the high efficiency of using microorganisms and macrophytes to neutralize ions of manganese, lead, chromium, iron, and strontium. Ultimately, the study argues for the viability of implementing integrated bio-sorption and phytoremediation technologies to restore the quality of both natural and waste waters.